(untitled) (Journal of Scientific Research, 2017)
Effective and cost efficient wastewater treatment is one of the major challenges for textile sectors of Bangladesh. The present study was an attempt to address the removal efficiency of organic matter and suspended solid of textile waste water by industrial scale combined anaerobic and aerobic treatment system. The experiments were performed at 6, 12, 18 and 24 hr hydraulic retention times (HRTs) and removal efficiency of different parameters (BOD5, COD and TSS) was measured. The average BOD5 and COD removal efficiency were in the range of 71% to 91% and 52% to 75% respectively at different HRTs in this plant. 73% - 82% range of TSS of wastewater was reduced by this method. Maximum BOD5 (88.2-92.5%) removal was occurred in aerobic treatment system whereas, high amount of COD (49.2-71.7%) removal efficiency reported in the anaerobic treatment system at different HRTs. The result indicated that the industrial scale combined treatment system can treat wastewater effectively.